EFFECTS OF ANXIOLYTICS ON THE ORGANISM OF BROILER CHICKENS (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
According to the results of the experiments conducted in this article, 100 one-day-old chicks of the Ross-308 cross breed were separated and placed on the bedding in a small chicken coop of the university. Their live weights were measured and 4 groups of 25 were formed. The first group was a comparative control group, and the chicks were fed with pure feed without any drugs. The chicks of the second experimental group were given 3.5 mg/kg of the drug Nozepam, and the chicks of the third experimental group were given 0.5 ml/l of 10% Enroflox antibiotic in water. The chicks of the fourth experimental group were given 1 mg/2 liters of water with Aliceril WS for 30 days. On days 7-15 of the experiment, blood was taken from the subwing vein of the chicks to determine the biochemical parameters of the blood serum and the total protein content in the blood serum was examined by refractometry.
Keywords: Chick, nozepam, bacteriocide, lysozyme, resistance, drug, stress, Aliceril WS, enroflox, antistressor, hypothalamus, pituitary gland.